Parenting - Empirical Advances and Intervention Resources 2018
DOI: 10.5772/intechopen.68933
|View full text |Cite
|
Sign up to set email alerts
|

Parental Self-efficacy in Promoting Children Care and Parenting Qualityvv

Abstract: Parental self-efficacy (PSE) emerges as a crucial variable into exploring variability in parenting quality. After introducing the link between PSE and parental competence, the role of PSE on parenting quality, its multiple influences, and transactional effects connected to contextual or cultural variables are discussed. The chapter addresses some key issues: (a) the levels of PSE measurement (i.e., domain-or task-specific approach), their interrelationship and magnitude as mutual predictors (study 1); (b) infa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 77 publications
3
30
0
3
Order By: Relevance
“…Parental beliefs include also self-efficacy [31,32], that is, parent's sense of competence in their own digital skills and in managing their children's technology usage. An example of parental self-referent estimation of competence is "I won't bother setting parental controls or passwords because my kids will "hack" around them" (cfr.…”
Section: Parental Media Competence and Self-efficacymentioning
confidence: 99%
“…Parental beliefs include also self-efficacy [31,32], that is, parent's sense of competence in their own digital skills and in managing their children's technology usage. An example of parental self-referent estimation of competence is "I won't bother setting parental controls or passwords because my kids will "hack" around them" (cfr.…”
Section: Parental Media Competence and Self-efficacymentioning
confidence: 99%
“…There are researches in the literature on how the development of maternal self-efficacy perception progresses from the birth of the infant. In the study of Benedetto and Ingrassia (5), a longitudinal course of maternal selfefficacy was observed in the postnatal period. The findings showed that there is a significant decrease in perceived maternal self-efficacy in the third month compared to the first month after birth, and it increases to the previous level in the first month around the sixth month.…”
Section: Introductionmentioning
confidence: 99%
“…Self-efficacy is a belief in one's abilities (Putarek & Pavlinbernardi, 2020). Parental self-efficacy emerges as a crucial variable in exploring variability in parenting quality (Benedetto et al, 2018). Parenting self-efficacy is a belief that one can successfully parent a child, which affects one's willingness to take on the role of their child's first teacher (Elizabeth et al, 2017).…”
Section: Problem Of Researchmentioning
confidence: 99%